ASUHAN KEPERAWATAN PADA PASIEN BRONKOPNEUMONIA : MASALAH POLA NAPAS TIDAK EFEKTIF DENGAN INTERVENSI POSISI SEMI FOLWLER - Ratu, Melky; Rohi, Elfrida; Billi, Sariyati (Program Studi Keperawatan, Universitas Timor Jln. Mgr. Sugyopranoto-Haliwen, 2025)
Bronchopneumonia is a type of pneumonia which is inflammation of the respiratory tract that occurs from the bronchi to the alveoli. The causes of bronchopneumonia can vary, namely bacteria, viruses, fungi, protozoa, and foreign substances. The aim of this case study is to determine the description of nursing care for children experiencing bronchopneumonia with a focus on the problem of ineffective breathing patterns in the semi-Fowler position. This type of research is a descriptive method, namely making a comparison between two clients. The subject in this case was a pediatric patient diagnosed with bronchopneumonia in the Dahlia room. The results of the study show that the problem of ineffective breathing patterns can be resolved by using nursing care, namely the semi-follower position where the criteria determined by the results of the implementation carried out by the patient have a response that shows the development of the patient's decreased dyspnea, decreased orthopnea, decreased nostril breathing, improved respiratory frequency, improved respiratory depth.